Outcome after resection for perihilar cholangiocarcinoma in patients with primary sclerosing cholangitis: an international multicentre study. Issue 11 (November 2021) - Jansson, Hannes; Olthof, Pim B.; Bergquist, Annika; Ligthart, Marjolein A.P.; Nadalin, Silvio; Troisi, Roberto I.; Groot Koerkamp, Bas; Alikhanov, Ruslan; Lang, Hauke; Guglielmi, Alfredo; Cescon, Matteo; Jarnagin, William R.; et al.
Abstract: Background: Resection for perihilar cholangiocarcinoma (pCCA) in primary sclerosing cholangitis (PSC) has been reported to lead to worse outcomes than resection for non-PSC pCCA. The aim of this study was to compare prognostic factors and outcomes after resection in patients with PSC-associated pCCA and non-PSC pCCA. Methods: The international retrospective cohort comprised patients resected for pCCA from 21 centres (2000–2020). Patients operated with hepatobiliary resection, with pCCA verified by histology and with data on PSC status, were included. The primary outcome was overall survival. Secondary outcomes were disease-free survival and postoperative complications. Results: Of 1128 pCCA patients, 34 (3.0%) had underlying PSC. Median overall survival after resection was 33 months for PSC patients and 29 months for non-PSC patients (p = .630). Complications (Clavien-Dindo grade ≥ 3) were more frequent in PSC pCCA (71% versus 44%, p = .003). The rate of posthepatectomy liver failure (21% versus 17%, p = .530) and 90-day mortality (12% versus 13%, p = 1.000) was similar for PSC and non-PSC patients. Conclusion: Median overall survival after resection for pCCA was similar in patients with underlying PSC and non-PSC patients. Complications were more frequent after resection for PSC-associated pCCA, with no difference in postoperative mortality.